Effect of Salinity Adaptation Technique on Survival and Growth Rate of Patin Catfish, Pangasius sp. - Nirmala, K.; Lesmono, D.P.; Djokosetiyanto, D. (Jurnal Akuakultur Indonesia, 2005)
This study was carried out to determine the effect of salinity adaptation techniques on growth and survival of patin catfish Pangasius sp. fry.  Fry of 1.5-2.0 inch in length were reared in the water with different of the initial salinity of 1, 2, 3, 4 and 5 ppt.  Salinity was then daily increased by duplicated the initial water salinity until fish died.  The results of study showed that fry could survive by initial salinity adaptation of 1 ppt and then increasing the salinity by 1 ppt/day to reach 27 ppt.  In the other treatments, all fry died after the salinity reach 18-25 ppt. Keywords: patin catfish, Pangasius, adaptation, salinity   ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh teknik adaptasi salinitas terhadap pertumbuhan dan kelangsungan hidup benih ikan patin Pangasius sp.  Benih patin ukuran 1,5-2 inci dipelihara pada salinitas awal berbeda, yaitu 1, 2, 3, 4 dan 5 ppt. Salinitas air pemeliharaan ditingkatkan kelipatan dari salinitas awal setiap hari hingga ikan mati.  Hasil penelitian menunjukkan bahwa adaptasi salinitas awal 1 ppt dan peningkatan sebesar 1ppt/hari menyebabkan ikan dapat bertahan hidup sampai pada salinitas 27 ppt. Pada perlakuan lainnya, benih ikan mengalami kematian masal ketika salinitas mencapai 18-25 ppt. Kata kunci: ikan patin, Pangasius, adaptasi, salinitas